An Intervention with an Adolescent Incest Victim/Abuser - Darou, Wes G. (Canadian Journal of Counselling and Psychotherapy, 1992)
Clinical work with clients who are both victims and also sexual abusers is complex and troubling. The present article describes one session of the treatment of a 14-year-old victim/ offender. The approach combines the story-telling technique of Richard Gardner and the fantasy work of Violet Oaklander. These methods are particularly useful for overcoming resistance. As counselling continues, however, the client must move towards a more conscious understanding in dealing with the problem to prevent recurrence of the incidents of abuse.